PERANAN PENYIDIK KEPOLISIAN RESOR ROKAN HILIR DALAM MEMBERANTAS TINDAK PIDANA PROSTITUSI - WINDA SUSTYA; Rika Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In combanting crime of prostitutions is not maximized because in addition to the facilities and infrastructureis also inadequatelack of encouragementfrom the comunity criminal act of prostitution has been a lot of standing, in trems of the law no one has set and regulated by law only pimps and pimp so investigator had dificulty, prostitution arises due to economic dificullties in finding jobs therefore peoples want to get a job and make money fast easy purpose of this thesis: first, to determine the role of police investigators resort Rokan Hilir, second, the barriers faced by the police in combating the resort Rokan Hilir crime of prostitution, third, the efforts made by investigators in combating the crime of prostitutionThis type of research can be classified in this type of juridical sociological research, because in this study the authors directly conduct research on the location or place under study in order to provide a complete and clear picture tenteng problems examined in this case, the source of the data used, the primary data, secondary data , and the data tertiary data collection techniques in this study were interviews, literature study, a questionnaire.there are three main things that can be inferred, the first police investigator role Rokan Hilir resort in combating the crime of prostitution, under Law No. 2 of 2002 the police as law enforcement is maintaining security and public order, enforce the law, provide protection, guidance, and service to the community one of them combat the crime of prostitution, police resort roikan downstream as possible to combat the crime of prostitution both, barriers faced by the police to resort Rokan Hilir is a very strategic geographical location, the difficulty of revealing evidence, lack of awareness and legal awareness, the third attempt Police investigators conducted Rokan Hilir in combating the crime of prostitution community policing efforts to prevent the establishment, conduct legal education formed a special team, investigating, investigation, raid, arrest pimps and pimping, impose penalties.Kunci : Peranan-Penyidik- Tindak Pidana Prostitusi